2016
DOI: 10.5897/jmpr2016.6219
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical survey of medicinal plants used in malaria management in South Benin

Abstract: In Bénin, malaria is a major public health concern, especially for children under five years and pregnant women. Considering the inefficiency of the health centers in some regions, people use plants for their primary health care. This study aimed to identify and document the medicinal plants used in the treatment of malaria in four departments (Littoral, Ouémé, Plateau and Zou) of south Bénin. Data were recorded using interview and field observation. 42 informants including 15 traditional healers and 27 medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous research reports, within and outside Nigeria, have highlighted the antimalarial values of Azadirachta indica (Iwu et al, 1986;Bhat et al, 1990;Aiyeloja and Bello, 2006;Ehiagbonare, 2007) and Vernonia amygdalina (Bhat et al, 1990;Asase et al, 2005), anti-pyretic value of Lantana camara (Lagnika et al, 2016), use of Senna alata (=Cassia alata) in the treatment of skin diseases/ringworm (Bhat et al, 1990), Sida cordifolia in the management of asthma (Bhat et al, 1990), Ocimium gratissimum as anti-diarrhoea/stomach upset (Aiyeloja and Bello, 2006), Bridelia micrantha (a relative of Bridelia ferruginea), Momordica charantia and Phyllantus amarus in the treatment of diabetes (Abo et al, 2008;Laleye et al, 2015), Clausena anisata in the treatment of stomach pain or abdominal disorder (Olajuyigbe and Afolayan, 2012) etc. Other plants mentioned in this study have also been known and reported to be useful in the management of diseases or disorders that are more or less related to the indications stated in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research reports, within and outside Nigeria, have highlighted the antimalarial values of Azadirachta indica (Iwu et al, 1986;Bhat et al, 1990;Aiyeloja and Bello, 2006;Ehiagbonare, 2007) and Vernonia amygdalina (Bhat et al, 1990;Asase et al, 2005), anti-pyretic value of Lantana camara (Lagnika et al, 2016), use of Senna alata (=Cassia alata) in the treatment of skin diseases/ringworm (Bhat et al, 1990), Sida cordifolia in the management of asthma (Bhat et al, 1990), Ocimium gratissimum as anti-diarrhoea/stomach upset (Aiyeloja and Bello, 2006), Bridelia micrantha (a relative of Bridelia ferruginea), Momordica charantia and Phyllantus amarus in the treatment of diabetes (Abo et al, 2008;Laleye et al, 2015), Clausena anisata in the treatment of stomach pain or abdominal disorder (Olajuyigbe and Afolayan, 2012) etc. Other plants mentioned in this study have also been known and reported to be useful in the management of diseases or disorders that are more or less related to the indications stated in this study.…”
Section: Discussionmentioning
confidence: 98%
“…However, this study revealed a more significant occurrence of such infections amongst herb users, which may have stemmed from variances in the herbs they used. Furthermore, while some herbs have been documented to merely suppress microorganisms, there exists a lack of scientific accreditation regarding their effectiveness as treatment, including an absence of established dosages [29]. Another factor that could have contributed to the high prevalence rate for herb users in this particular study is the harvesting time and processing method used, as suggested by Oladunmoye and Kehinde [28].…”
Section: Discussionmentioning
confidence: 99%
“…Ethnobotanical and ethnopharmacological surveys carried out in African and Asian countries have reported the use of M. oleifera for the treatment of malaria in traditional communities [31][32][33][34][35][36][37][38]. These ethnomedicinal uses have been confirmed through in vivo and in vitro assays using different products obtained from the leaves and seeds of M. oleifera against several malaria-causing species of Plasmodium [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 92%
“…Ethnobotanical and ethnopharmacological surveys carried out in Nigeria have highlighted the constant use of M. oleifera leaves for the treatment of malaria by traditional communities in the country [54][55][56][57][58][59][60][61]. Other African countries that also stood out in the use of M. oleifera leaves were Uganda [36,62,63], Benin [31,64,65], and Ghana [66][67][68]. Scientific research shows that extracts from the leaves of this plant had in vivo antimalarial activity [69][70][71][72], confirming its use in traditional medicine.…”
Section: Ethnomedicinal Uses Of Moringa Oleifera For the Treatment Of...mentioning
confidence: 99%